2003
DOI: 10.1590/s0103-90162003000300027
|View full text |Cite
|
Sign up to set email alerts
|

Reference evapotranspiration estimation inside greenhouses

Abstract: Because of the large area occupied by a class A pan, alternative methods have been sought to estimate reference evapotranspiration (Eto) inside greenhouses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 4 publications
2
29
0
6
Order By: Relevance
“…Only a limited number of national publications specialized in this area compare the ETc values for greenhouse irrigated crops using these methods with studies of water balance using lysimeters. Although the use of ANE in greenhouses has not been reported in international research, the other methods in the present study have been evaluated under these conditions for several crops (Fernandes et al, 2003;Blanco and Folegatti, 2003;2004;Orgaz et al, 2005), although few with lettuce (Galvani et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Only a limited number of national publications specialized in this area compare the ETc values for greenhouse irrigated crops using these methods with studies of water balance using lysimeters. Although the use of ANE in greenhouses has not been reported in international research, the other methods in the present study have been evaluated under these conditions for several crops (Fernandes et al, 2003;Blanco and Folegatti, 2003;2004;Orgaz et al, 2005), although few with lettuce (Galvani et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For the evapotranspiration inside the greenhouse [20] observed that the reference Evapotranspiration (ETo) inside greenhouses was always lower, with a range of 45-77% of that verified outside [21]. The water loss from the land to the atmosphere due to Evapotranspiration (ET) can be divided into two losses, evaporation and transpiration.…”
Section: Preliminary Data Analysismentioning
confidence: 99%
“…For the evapotranspiration inside the greenhouse [20] observed that the reference Evapotranspiration (ETo) inside greenhouses was always lower, with a range of 45-77% of that verified outside [21].…”
Section: Preliminary Data Analysismentioning
confidence: 99%
“…Similarly, the strawberry grower (site 3) produced strawberries in an open field (zone 4) as well as under plastic high tunnels (zone 5), and both management practices were monitored. Crop water requirements are recognized to be approximately 30% lower in production systems under a high tunnel (Monterro et al, 1985;Rosenberg et al, 1989;Fernandes et al, 2003;Harmanto et al, 2005). It was therefore relevant to compare how water requirements were met by the participant producer in these different production systems.…”
Section: Site Descriptionsmentioning
confidence: 99%
“…For this study, crop coefficients were derived from OMAFRA (2004) and Van der Gulik (2001). The influence of a greenhouse on (Rosenberg et al, 1989;Fernandes et al, 2003;Harmanto et al, 2005).…”
Section: Swcmentioning
confidence: 99%